Ectopic Fat Depots and Coronary Artery Calcium in South Asians Compared With Other Racial/Ethnic Groups. Issue 11 (November 2016) - Garg, Sachin K.; Lin, Feng; Kandula, Namratha; Ding, Jingzhong; Carr, Jeffrey; Allison, Matthew; Liu, Kiang; Herrington, David; Vaidya, Dhananjay; Vittinghoff, Eric; Kanaya, Alka M.
Abstract : Background: South Asians have a low body mass index and high prevalence of cardiovascular disease (CVD) relative to other racial/ethnic groups. Radiographically detected ectopic fat distribution is better associated with CVD than body mass index. We assessed whether differences in ectopic fat depots explained differences in the prevalence/severity of coronary artery calcium (CAC), a predictor of incident CVD events, among South Asians compared with other racial/ethnic groups. Methods and Results: We examined the associations of radiographically detected visceral, intermuscular, intrahepatic, and pericardial fat with CAC among adults without baseline CVD. We compared 803 South Asians in the Mediators of Atherosclerosis in South Asians Living in America to 4 racial/ethnic groups in the Multi‐Ethnic Study of Atherosclerosis: 2622 whites, 1893 blacks, 1496 Latinos, and 803 Chinese Americans. We adjusted for body mass index and known CVD risk factors. South Asians had the highest intrahepatic fat and lowest pericardial fat volume (PFV). There was a positive graded association between ectopic fat and higher CAC scores in all the groups with the strongest associations observed with PFV. PFV was independently associated with CAC severity in South Asians ( P =0.01) and blacks ( P =0.05) and borderline in whites ( P =0.06). PFV partially explained the higher CAC burden in South Asians compared with blacks, but not the other racial/ethnic groups. Conclusions: Differences in PFV explain a small fraction of the higher CAC burden in South Asians. Our findings suggest that ectopic fat depots may not explain the elevated CAC risk in South Asians.